Approach To The First Unprovoked Seizure- PART I - GHOFRANI, Mohammad (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Ghofrani M. Approach To The First Unprovoked Seizure- PART I. Iran J Child Neurol. 2013 Summer; 7(3): 1- 5. The approach to a child who has experienced a first unprovoked generalized tonic-clonic seizure is challenging and at the same time controversial. How to establish the diagnosis, ways and means of investigation and whether treatment is appropriate, are different aspects of this subject. In this writing the above mentioned matters are discussed. References 1. Bluvstein JS, Moshe SL. First unprovoked seizure Current Management in child Neurology, third ed. 2005.P.89-92. 2. Hirtz D, Berg A, Bettis D, et al. Practice Parameter: treatment of the child with a first unprovoked seizure. American Academy of Neurology 2003;60:166-175. 3. Verity GM, Ross EN, Golding J. Epilepsy in the first ten years of life: finding of the child health and education study. Br Med J 1992;305:857-861. 4. Camfiled CS, Camfield PB, Gordon K, et al. Incidence of epilepsy in childhood and adolescence: A populationbased study in Nova Scotia from 1977 to 1985. Epilepsia 1996;37:19-23. 5. Hauser W, Annegers J, Kurland L. Incidence of epilepsy and unprovoked seizure in Rochester, Minnisota, 1935- 1984. Epilepsia 1993;34:453-468. 6. Jallon P, Goumaz M, Haenggeli G, Morabia A. Incidence of first epileptic seizure in the canton of Geneve Switzerland. Epilepsia 1997;38:547-552. 7. Camfiled PR, Camfiled CS. Pediatric Epilepsy: An overview. Swaiman’s pediatric Neurology, 5th ed, 2012. P.703-710. 8. Gowers WB. Epilepsy and other chronic convulsive diseases; their causes, symptoms and treatment. London: J&A Churchill,1881. P.242. 9. Goddard GV, Mc Intyre DC, Leech CK. A permanent change in brain function resulting from daily electrical stimulation- Exp Neural 1969;25:295-330. 10. Berg AT, Shinnar S. Do seizures beget seizure? An assessment of the clinical evidence in human. J Clinical Neurophysiol 1993: 14: 102-110. 11. Wasterlain CG. Recurrent seizures in developing brain are harmful. Epilepsia 1997;38:728-734. 12. Meldrum B. Physiologic changes during prolonged seizure and epileptic brain damage. Neuropediatric 1978;9:203-212. 13. Chen K, Baram TZ, Soltesz I. Febrile seizure in developing brain results in persistent modification of neuronal excitability in limbic circuits. Nat Med 1999;5:888-894. 14. Schemid B, Tandon P, Stafstrom CE, Holmes CL. Effect of neonatal seizures on subsequent seizure-induced brain injury. Neurology 1999;53: 1754-1761. 15. Camfeild PB. Recurrent seizures in the developing brain are not harmful. Epilepsia 1997; 38:735-737. 16. Maytal J, Shinnar S, Moshe SL, Alvarez LA. Low morbidity and mortality of status epilepticus in children.Pediatrics 1989; 83:323-331. 17. Harvey As, Nolan T, Carlin JB. Community-Based study of mortality in children with epilepsy. Epilepsia 1993;34:597-603. 18. Callenbach PM, Westendorp RG, Geerts At, et al. Mortality risk in children with epilepsy: The Dutch Study of epilepsy in childhood. Pediatrics 2001;107:1259-1263. 19. Donner EJ, Smith CR. Snead OC. Sudden unexplained death in children with wpilepsy. Neurology 2001;57: 430- 434. 20. Camfield CS, Camfiels PR, Veugelers P. Deathe in children with epilepsy; A population-based study. Lancet 2002;315:1891-1895. 21. Austin JK. Concerns and fears of children with seizures. Clin Nurs Practice Epilepsy 1993;1:4-10. 22. Shinnar Sh, O’Dell Ch, Mitnick R, et al. Neuroimaging abnormalities in children with an apparent first unprovoked seizure. Epilepsy Research 2001;43:261-269. 23. Bachman DS, Hodges F, Freeman JM. Computerized axial tomography in chronic seizure disorders of childhood. Pediatrics 1976;58:828-832. 24. Nordli DR, Pedley TA. Evaluation of Children with seizure. In: shinnar S, Amir N, Branski D (Eds). Childhood Seizure. S. Kagerm Basel, 1995.P.66-77. 25. Gilliam F, Wyllie E. Diagnostic testing of seizure disorders. Neurolo Clin 1996;14: 61-84. 26. Kuzniecky RI. Neuroimaging in pediatric epilepsy. Epilepsia 1996;37:S10-S21. 27. Scheuer ML, Pedly TA. The evaluation and treatment of seizure. N Eng J Med 1990;232:1468-1474. 28. Greenberg MK, Barsan WG, Starkman S. Neuroimaging in the emergency patient with seizure.Neurology 1996 47;26-32. 29. King MA, Newton MR, Graeme Gh, et al. Epileptology of the first seizure presentation: A clinical, electroencephalographic and magnetic Resonance Imaging study of 300 consecutive casese. Lancet 1998;352:1007-1011. 30. Hirtz D, Ashwal S, Berg A, et al. Practice Parameter. Evaluating a first nonfebrile seizure in children. Report of the quality standards subcommittee of the American Academy of Neurology, The Child Neurology Society. Neurology 2000;55:616-623.